Revisiting Financial Performance in Conventional Banking: An Integrated Analysis of Liquidity, Solvency, and Profitability Ratios - Kusuma Wijaya; Siti Mujanah; Abdul Halik (Journal of Finance, Economics and Business, 2026)
This study examines the influence of liquidity, solvency, and profitability ratios on the financial performance of conventional banks listed on the Indonesia Stock Exchange during the 2021–2025 period. Using a quantitative explanatory approach, this study analyzed secondary data obtained from audited annual financial statements from 15 selected banks through purposive sampling, resulting in 75 observations. Financial performance is evaluated through financial ratio analysis, including liquidity measured by Loan to Deposit Ratio (LDR), solvency measured by Capital Adequacy Ratio (CAR), and profitability measured by Return on Assets (ROA) and Return on Equity (ROE). Data analysis was carried out using multiple linear regression supported by classical assumption test, t-test, F-test, and determination coefficient analysis. These findings reveal that liquidity, solvency, and profitability ratios significantly affect financial performance both partially and concurrently. Liquidity shows a positive contribution to operational stability and financial flexibility, while solvency reflects the importance of effective management of capital structures in maintaining banking resilience. Profitability emerged as an important indicator of managerial efficiency and sustainable performance. In addition, this model accounts for 99.5% variation in financial performance, demonstrating strong explanatory capabilities. This study highlights the importance of a balanced financial management strategy in improving the sustainability and competitiveness of banking. These findings contribute to the literature on the financial performance of banks and provide practical implications for banking management and financial regulators in strengthening financial stability and operational efficiency.